FACILITIES OF LOCALIZATION AND NEUTRALIZATION OF GASSINGS FOR THE BAR DEPARTMENTS OF CASTING HOUSES - Ju. P. Shapovalov; A. S. Galibus; A. V. Pribylov (Литьë и металлургия)
The absorbation-biochemical method, based on using of the solution on the basis of the industrial water as an absorbent for clearing of ventilation air is developed.